Etični vidik nadležnih elektronskih sporočil (spama) - Bračko, Davor (Organizacija znanja, 2008)
This paper presents various aspects concerning recipients of unsolicited e-mail advertising - spam; in many cases, the unethical nature of such advertising has been established. Spam ethics has been assessed from various aspects of ethical theories, which use different methods to evaluate the motivation to perform an act and various criteria to determine the ethics; they put either an individual or society to the forefront (some theories are more subjective, whereas others are more objective). Spam can be sent in an intrusive way. The identity of the sender is unknown, the content of messages inappropriate, misleading or malicious and the volume of messages unacceptable; in addition to this, the recipient has no possibility to avoid receiving such messages. When the sender does not take into account all the conditions that make an e-mail acceptable for the recipient, it can be stated that it is an unsolicited e-mail or spam. Spam is only one of many risks that can affect Internet users, exploiting primarily their ignorance; the fragilityof the Internet is compromised by spam. All Internet users bear moralresponsibility for the vulnerability of the Internet community and they should constantly strive to remain within the morally acceptable frame. Unfortunately, the Internet is no exception and striving to remain within the morally acceptable frame is not in the interest of all.
Keywords: advertising; elektronska pošta; ethics; etika; internet; nadležna sporočila; oglaševanje; SPAM; varovanje zasebnosti